TUBERCULOSIS CONTROL; WHERE DO WE STAND TODAY IN PAKISTAN - Javaid, Arshad (Journal of Postgraduate Medical Institute, 2011)
Tuberculosis (TB) is a bacterial infection c a u s e d b y t h e o r g a n i s m s b e l o n g i n g t o Mycobacterium Tuberculosis complex and is spread by droplet infection 1 . It is an ancient disease well known for the last 5000 years but still is infecting one third of the world population and is a major public health problem globally.